(untitled) (Philosophy and Progress, 2023)
Hazrat Sharafuddin bin Yahyah Maneri was a scholar and Sufi of the thirteenth-fourteenth centuries. He was a prolific writer. One of his important books is a collection of letters titled Maktubat-i-Sadi. The article focuses to bring out the main themes of the book and identified ten topics to discussed. They are: 1. Concept and love of God; 2. Deceiving nature of the world; 3. Sin and repentance; 4. Necessity of a qualified spiritual guide and obedience to his guidance; 5. Origin and need of Sufism; 6. Poverty and its role in the purification of evil soul; 7. Rendering selfless service to others; 8. Fate and predestination; 9. Observance of the Shariah; and 10. Acquisition of good qualities and shunning of the evil ones. The philosophical and spiritual significance of these teachings have been pointed out in this article. Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 79-96